The approach to headache of the adult-elderly patient in an Italian homeopathic surgery: The rules of the visit according to Hahnemannian uniqueness - Magro, Valerio M (Indian Journal of Integrative Medicine, 2023)
Headache is a disorder that can also be disabling. Although the prevalence declines with age, headache remains a common neurologic complaint among elderly people. Homeopathy, by not suppressing, facilitates the free transit of the healing current from the inside to the surface (temporary aggravation), so that a harmonious balance is restored and healing is, this time, lasting. This is why it benefits from the homeopathic remedy. The choice of remedy is a delicate and difficult moment. We discuss taking care of the elderly patient afflicted by headaches through a homeopathic evaluation of the symptoms and of the patient as a whole, through a methodology that ultimately leads to the choice of the only homeopathic remedy that will constitute the patient's therapy, by reviewing the various characteristics of homeopathic remedies or better of the headaches caused by them, in order to then obtain the simillimum.